Design of a Banana Fiber-Extracting Machine. - Lejoruku, David Desire (Kabale University, 2025)
Banana fiber offers a superior alternative to synthetic and natural fibers, boasting eco-friendliness, chemical-free, non-toxic, and odorless properties. However, traditional extraction methods can be labor-intensive and yield variable results. This study seeks to overcome these limitations by developing an electric-powered banana fiber extraction machine. The approach involves material selection, design, fabrication, and assembly of machine components. The developed machine aims to reduce processing time and enhance product quality through improved blade design, optimized roller spacing, and sufficient motor torque. These modifications enable efficient fiber separation, minimize damage, and produce high-quality fibers. The expected outcome is a significant reduction in plantain fiber production time.